An Insight Into the microRNA Profile of the Ectoparasitic Mite Varroa destructor (Acari: Varroidae), the Primary Vector of Honey Bee Deformed Wing Virus - Kumar, Deepak; Alburaki, Mohamed; Tahir, Faizan; Goblirsch, Michael; Adamczyk, John; Karim, Shahid (Frontiers in Cellular and Infection Microbiology, 2022)
The remarkably adaptive mite Varroa destructor is the most important honey bee ectoparasite. Varroa mites are competent vectors of deformed wing virus (DWV), and the Varroa-virus complex is a major determinant of annual honey bee colony mortality and collapse. MicroRNAs (miRNAs) are 22-24 nucleotide non-coding RNAs produced by all plants and animals and some viruses that influence biological processes through post-transcriptional regulation of gene expression. Knowledge of miRNAs and their function in mite biology remains limited. Here we constructed small RNA libraries from male and female V. destructor using Illumina’s small RNA-Seq platform. A total of 101,913,208 and 91,904,732 small RNA reads (>18 nucleotides) from male and female mites were analyzed using the miRDeep2 algorithm. A conservative approach predicted 306 miRNAs, 18 of which were upregulated and 13 downregulated in female V. destructor compared with males. Quantitative real-time PCR validated the expression of selected differentially-expressed female Varroa miRNAs. This dataset provides a list of potential miRNA targets involved in regulating vital Varroa biological processes and paves the way for developing strategies to target Varroa and their viruses.